Impact of the Mobile Banking Application Ratings on the Vietnamese Bank Service Income - Pham, Tien Phat; Popesko, Boris; Hoang, Sinh Duc; Tran, Tri Ba (Comparative Economic Research. Central and Eastern Europe, 2023)
Based on the relationship between fintech and bank performance and the role of mobile applications in bank operations, we investigate the impact of mobile banking application (MBA) ratings on bank service income. The quarterly data from the 15 biggest Vietnamese commercial banks in 2019–2020 were extracted from the public financial statements and the Google Play Store. The Generalized Least Squares method is applied to process the proposed regression models. We find a positive impact of MBA ratings on bank service income. We additionally explore the MBA quality of a large bank that does not meet customer expectations and how the interaction between MBA ratings and leverage harms bank service income. Finally, users generally appreciate the MBA quality, and COVID–19 does not affect the link between MBA ratings and bank service income. The study provides novel knowledge on customer behavior through MBA ratings and their effect on bank service income in an emerging country.